THE IMPLEMENTATION OF ARIMA METHOD IN FORCASTING INDONESIAN CRUDE OIL EXPORT, PRODUCTION AND CONSUMPTION - Sarfiah, Sudati Nur; Aripulis, Arina Sabilarrochmah (Universitas Tidar, 2023)
Petroleum is one of the main sources of energy consumed by the Indonesian people. Indonesia, one of the major oil producers in the world, is currently facing the possibility of oil shortages. Petroleum-based energy sources have limited supplies if they continue to be used. The lack of alternative energy produced to replace petroleum is the reason behind the increasing use of petroleum. To meet domestic oil demand in this scenario, appropriate strategies and policies are needed. Using historical data from 1990-2022, this analysis attempts to project Indonesia's petroleum exports, production, and consumption in 2023-2027. This study uses the Auto-Regressive Integrated Moving Average or ARIMA method with the best model for forecasting exports, production, and consumption being (1, 1, 1), (1, 1, 0), and (2, 1, 0), respectively. From the results of the study, it is predicted that oil exports and production have decreased far below oil consumption which shows an increase. This can have a negative impact on the Indonesian economy. Thus, this research can be used as a reference for future policy-making